Analisis Pengaruh Belanja Pemerintah Daerah Berdasarkan Klasifikasi Ekonomi Terhadap Pertumbuhan Ekonomi Regional di Indonesia - Fitrianty, Dwinta; Lestari, Nur Indah (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2024)
Economic growth is a primary development goal. While national economic growth trended upwards 0,16% from 2014 to 2018, a different trend emerged at the provincial level. In the other side, regional government spending, that bolster local economic growth, across all provinces and districts/cities has increased. Hence, despite rising spending in many regions, economic growth trends downward. This study seeks to analyze whether local government spending, classified by economic category, influences regional economic growth. Using data of 37 provinces and applying Panel ECGLS, regression data presents mixed findings. Capital expenditure, interest expenditure, social transfer expenditure, and unexpected expenditure show statistically negative and significant effects on economic growth, while other expenditure components do not. This suggests that local government spending is ineffective and crowds out private consumption, leading to a decline in regional economic growth.